International regulation of virtual assets under FATF's new standards. Issue 1 (7th July 2020) - Pavlidis, Georgios
Abstract : Purpose: To critically examine two significant developments for the regulation and supervision of virtual assets and virtual assets services providers: the amendment of the Financial Action Task Force (FATF) Recommendation No 15 in October 2018 and the adoption of an Interpretative Note in June 2019. We argue that new FATF standards constitute an appropriate response to money laundering and terrorist financing risks associated with virtual assets, but that they must be followed by firm, consistent and effective implementation at the national level. Design/methodology/approach: This paper draws on reports, legislation, legal scholarship and other open source data in order to examine the new FATF standards on virtual assets. Findings: The amendment of the FATF Recommendation No 15 in October 2018 and the adoption of an Interpretative Note in June 2019 have been necessary and opportune to forge a global approach to mitigate money laundering risks associated with crypto-assets. The new FATF standards on crypto-asset activities need to be implemented firmly, effectively and consistency to reduce the risk of jurisdiction-shopping by money launderers and terrorism financiers. Originality/value: This is one of the first studies examining two important and recent FATF initiatives, the amendment of the FATF Recommendation No 15 in October 2018 and the adoption of an Interpretative Note in June 2019.